Feelings Are Always Local - Brouwer, Joke (Rotterdam V2_Publishing, 2005)
Interactive art is organized as an open system: it is able to exchange matter, energy, and information with its environment while maintaining its coherence. Interactive art is art in a state of rest that must be disturbed: it is a system that has to become network before it becomes art at all. In order to come to grips with the phenomenon of interactive art, one must first understand the relationship between systems and networks. To find form or to see form arise, seek the systems in the network.'Feelings Are Always Local' analyzes the ways in which networks organize, expand, come together, and rearrange themselves from the inside out. With the help of specific examples, the authors investigate how we live in networks, how possibilities are created within them, opportunities seized, escape routes chosen and how things sometimes go utterly wrong. The first question is scientific in nature: How do networks function? The second is political: How are networks made manageable at the concrete, everyday level?'Feelings are Always Local' was published on the occasion of DEAF04, the 2004 Dutch Electronic Arts Festival, which focused on interactivity as an open system and interactivity in open systems. The book looks at projects with a social and political slant as well as those with a technological or biological character. It includes a series of essays, interviews and projects by international theorists and artists.
Introduction - Feelings Are Always Local / Arjen Mulder & Joke Brouwer -- Minorities and the Production of Daily Peace / Arjun Appadurai -- Planet of Slums / Mike Davis -- In Defiance of Existence: Notes on Networks, Control and Life Forms / Alexander Galloway & Eugene Thacker: Every Species Is The Embodiment of Experience with the World / Tijs Goldschmidt -- Opening the Brown Box: Networks, Science and Infrastructure / Christopher Kelty -- Ludwig von Bertalanffy's Biological Worldview / Arjen Mulder -- Memories are Constructive in Nature / Karim Nader -- The New Economy of Terror / Loretta Napoleoni -- 0100101110101101.org: Perpetual Self Dis-Infecting Machine -- Onewordmovie / Beat Brogle and Philippe Zimmermann -- Si Poteris narrare / Jean-Michel Bruyère -- All Is Full of Love / Chris Cunningham -- Utopia Travel / Emanuel Danesch and David Rych -- Civilization IV / Eastwood -- Zhang Ga / Peoples' Portrait -- Bitmirror / Tobias Grewenig -- OnesAndZeros / Axel Heide -- UnMovie / Philip Pocock & Gregor Stehle -- Tide / Luke Jerram -- Ohrwurmbeschleuniger / Roman Kirschner -- Perm / Ulf Langheinrich -- Gravicells / Seiko Mikami and Sota Ichikawa -- Mobile Cartographic Command Center -- TramJam / Mumbai Streaming Attack -- Run Motherfucker Run / Marnix de Nijs -- n-cha(n)t / David Rokeby -- Very Slow Scan Television / Gebhard Sengmüller -- WIMP / Alexei Shulgin, Victor Laskin -- Mobile Feelings / Christa Sommerer and Laurent Mignonneau -- Membrane / Sponge -- The Bar Bot / Time's Up -- DEVMAP / Workspace Unlimited -- M.U.S.H. / Joachim Montessuis and Eléonore Hellio
Keywords: 21st Century (2001-2100); Artistic research; Experience